A new species of Ituglanis (Siluriformes: Trichomycteridae) from the Tocantins and Paranaíba river basins, central Brazil, with remarks on the systematics of the genus - Datovo, Aléssio; Aquino, Pedro De Podestà Uchôa De; Langeani, Francisco (Zootaxa, 2016)
Ituglanis goya, new species, is described from the Paranaíba and Tocantins river drainages, central Brazil. This is the first species of the genus described for the Upper Paraná system and the second epigean Ituglanis for the Tocantins basin. The new species is distinguished from its congeners by the combination of a color pattern formed by longitudinal stripes and spots, absence of the anterior cranial fontanel, pattern of the cephalic laterosensory system and several fin-ray counts. Ituglanis goya exhibits morphological features that oppose the traditional hypotheses of alignment of the genus with the TSVSG clade of Trichomycteridae. These and other issues concerning the systematics of Ituglanis and the Trichomycterinae are critically discussed.